Стратегічне управління як фактор економічної безпеки підприємства - Толбатов, А. В.; Tolbatov, A. V.; ORCID: http://orcid.org/0000-0002-9785-9975; В’юненко, О. Б.; Viunenko, O. B.; ORCID: http://orcid.org/0000-0002-8835-0704; Толбатов, С. В.; Tolbatov, S. V.; ORCID: http://orcid.org/0000-0003-2251-7409; Виганяйло, С. М.; Vyhaniailo, S. M.; ORCID: http://orcid.org/0000-0001-5350-0728; et al. (Modern Engineering and Innovative Technologies. – 2019. – Issue 10, part 2. – P. 34-39, 2019)
Економічна безпека підприємства забезпечує здатність підприємства до розвитку, підвищення конкурентоспроможності своєї продукції, утримання позиції підприємства на конкурентних ринках, силу та економічний потенціал підприємства для протидії негативному впливу зовнішнього та внутрішнього середовища. Економічна безпека підприємства забезпечує захист від загроз в довгостроковій перспективі.

The economic security of the enterprise provides the ability of the enterprise to develop, increase the competitiveness of its products, maintain the position of the enterprise in competitive markets, strength and economic potential of the enterprise to counteract the negative impact of the external and internal environment. The economic security of the enterprise provides protection against threats in the long run.

Экономическая безопасность предприятия обеспечивает способность предприятия к развитию, повышение конкурентоспособности продукции, содержание позиции предприятия на конкурентных рынках, силу и экономический потенциал предприятия для противодействия негативному влиянию внешней и внутренней среды. Экономическая безопасность предприятия обеспечивает защиту от угроз в долгосрочной перспективе.
Strategic management as a factor of economic security of the enterprise
Стратегічне управління як фактор економічної безпеки підприємства / Толбатов А. В., В’юненко О. Б., Толбатов С. В. та ін. // Modern Engineering and Innovative Technologies. – 2019. – Issue 10, part 2. – P. 34-39. – DOI: https://doi.org/10.30890/2567-5273.2019-10-02-026.
Толбатов, А., С. Толбатов, В. Толбатов, А. Вьюненко, и С. Виганяйло. «СТРАТЕГИЧЕСКОЕ УПРАВЛЕНИЕ КАК ФАКТОР ЭКОНОМИЧЕСКОЙ БЕЗОПАСНОСТИ ПРЕДПРИЯТИЯ». Modern Engineering and Innovative Technologies, т. 2, вып. 10-02, декабрь 2019 г., сс. 34-39, doi:10.30890/2567-5273.2019-10-02-026.
Keywords: Економічні науки. Економічна безпека. Economics. Economic Security. Экономические науки. Экономическая безопасность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; економічна безпека; економічна безпека підприємства; економічна стійкість; economic security; economic security of the enterprise; economic stability; экономическая безопасность; экономическая безопасность предприятия; экономическая устойчивость